6.9k views
5 votes
Complete the recursive formula of the arithmetic sequence -3, -1, 1, 3,...

b(1)= "answer"
b(n)=b(n-1)+ "answer"

User Culmat
by
4.3k points

1 Answer

0 votes

Given:

The given arithmetic sequence is:


-3,-1,1,3,...

To find:

The recursive formula of the given arithmetic sequence.

Solution:

We have,


-3,-1,1,3,...

Here, the first term is -3. So,
b(1)=-3.

The common difference is:


d=-1-(-3)


d=-1+3


d=2

The recursive formula of an arithmetic sequence is:


b(n)=b(n-1)+d

Where, d is the common difference.

Putting
d=2, we get


b(n)=b(n-1)+2

Therefore, the recursive formula of the given arithmetic sequence is
b(n)=b(n-1)+2, where
b(1)=-3.

User CodingHero
by
4.8k points